Stranger shores : essays 1986-1999 - Coetzee, J. M., 1940-; Text Publishing (Melbourne, Victoria : The Text Publishing Company, 2021)
Stranger Shores is the first of three collections of literary criticism by J. M. Coetzee to be republished by Text. It includes essays on Dostoevsky and Kafka, A. S. Byatt and Doris Lessing. These are concise, accessible introductions to some of the world's greatest writers, by a contemporary master. J. M. Coetzee was the first author to win the Booker Prize twice and was awarded the Nobel Prize for Literature in 2003. His work includes Waiting for the Barbarians, Life & Times of Michael K, The Master of Petersburg, Disgrace and Diary of a Bad Year. His most recent writing is a trilogy of novels: The Childhood of Jesus, The Schooldays of Jesus and The Death of Jesus. He lives in Adelaide. 'Freed from literary convention, Mr Coetzee writes not to provide answers, but to ask great questions.' Economist 'For all the sharpness and sorrow of Coetzee's writing, there is something grandly calming about his style: his sentences seem to give off light, and not in a hard dazzle, but in the glow of a child's night-light.' Age.
First published in the UK by Secker & Warburg, 2001.
Includes bibliographical references.
General.
Keywords: Criticism; Literature -- History and criticism; Criticism; Literary Collections - Essays; Literary Criticism - General; Literary essays; Literature; Electronic books; Criticism, interpretation, etc